An Activating Janus Kinase-3 Mutation Is Associated with Cytotoxic T Lymphocyte Antigen-4-Dependent Immune Dysregulation Syndrome - Sic, Heiko; Speletas, Matthaios; Cornacchione, Vanessa; Seidl, Maximillian; Beibel, Martin; Linghu, Bolan; Yang, Fan; Sevdali, Eirini; Germenis, Anastasios E.; Oakeley, Edward J.; Vangrevelinghe, Eric; Sailer, Andreas W.; et al. (Frontiers in Immunology, 2017)
Heterozygous mutations in the cytotoxic T lymphocyte antigen-4 (CTLA-4) are associated with lymphadenopathy, autoimmunity, immune dysregulation and hypogammaglobulinemia in about 70% of the carriers. So far, the incomplete penetrance of CTLA-4 haploinsufficiency has been attributed to unknown genetic modifiers, epigenetic changes or environmental effects. We sought to identify potential genetic modifiers in a family with differential clinical penetrance of CTLA-4 haploinsufficiency. Here we report on a rare heterozygous gain-of-function mutation in JAK3 (p.R840C) which is associated with the clinical manifestation of CTLA-4 haploinsufficiency in a patient carrying a novel loss-of-function mutation in CTLA-4 (p.Y139C). While the asymptomatic parents carry either the CTLA-4 mutation or the JAK3 variant, their son has inherited both heterozygous mutations and suffers from hypogammaglobulinemia combined with autoimmunity and lymphoid hyperplasia. Although the patient’s lymph node and spleen contained many hyperplastic germinal centers with follicular helper T (TFH) cells and immunoglobulin (Ig) G-positive B cells, plasma cell and memory B cell development was impaired. CXCR5+PD-1+TIGIT+ TFH cells contributed to a large part of circulating T cells but they produced only very low amounts of interleukin (IL)-4, IL-10 and IL-21 required for the development of memory B cells and plasma cells. We therefore suggest that the combination of the loss-of-function mutation in CTLA-4 with the gain-of-function mutation in JAK3 directs the differentiation of CD4 T cells into dysfunctional TFH cells supporting the development of lymphadenopathy, hypogammaglobulinemia and immunodeficiency. Thus, the combination of rare genetic heterozygous variants that remain clinically unnoticed individually may lead to T cell hyperactivity, impaired memory B cell and plasma cell development resulting finally in combined immunodeficiency.